A New Perspective for Construction Supply Chains in Digital Era - Koctas-Cotur, Ozlem; OZKAN OZEN, Yesim Deniz; Ozturkoglu, Yucel (International Journal of Sustainable Construction Engineering and Technology, 2024)
The construction industry is a highly labor-intensive industry with a low degree of automation and digitization. However, as in the manufacturing industry, a 'new order' is emerging for the way the construction industry works today. This study aims to present the transformation of construction supply chains (CSCs) in Industry 4.0 by considering each supply chain stage separately, where the main purpose is to determine the criteria for the integration of the CSC with the Industry 4.0 perspective. A literature review and a Delphi study were conducted, and thirteen criteria are proposed to show the integration of Industry 4.0 aspects and CSC stages. Furthermore, one of the multi-criteria decision-making (MCDM) methods, the Best-Worst method, is used to prioritize the criteria for guiding future implications during the transformation of construction supply chains. Among the six CSC stages, the design stage is the most important from the Industry 4.0 perspective. In addition, client collaboration by ICT (BIM) during the design phase is the most important sub-factors’ overall rank. Although there is a limited number of studies on the CSC, there are no empirical studies addressing the current digital age approach. As a result, there is a significant gap in the construction literature, and a thorough assessment of the building supply chain in an Industry 4.0 setting is lacking. To the best of the authors' knowledge, this is the first study to illustrate the transformation of CSCs in Construction 4.0 by looking at each supply chain stage separately.